Deciphering the molecular pathway of an asiaticosiderich fraction of Centella asiatica as an anti-melanogenesis agent - Agustina Setiawati; Brigitta Amanda Maharani; Putu Addelia Puspa Sari; K. Ariex Widyantara; Bakti Wahyu Saputra; Rifki Febriansah; Rini Dwiastuti (Journal of HerbMed Pharmacology)
Introduction: Melanin is a defense against UV radiation; however, it leads to significant cosmetic issues mainly melasma and hyperpigmentation. This study evaluated the potential effect of ethyl acetate (EtOAc) fraction of Centella asiatica extract in vitro inhibition activity against tyrosinase (TYR). Bioinformatics and in silico experiments were also employed to predict molecular pathways of asiaticoside, as the main active compound. Methods: Centella asiatica was extracted with ethanol and then fractionated with EtOAc. The fraction was tested in vitro for TYR inhibitory activity, and its active compounds were investigated using thin-layer chromatography (TLC). After obtaining the online database of the genes related to pigmentation and melanogenesis in the skin, the genes affected by asiaticoside were determined by the Venn diagram. The top 10 target proteins, underlying molecular pathways, got from CytoHubba, were further studied to figure out their molecular pathway. The molecular docking was conducted on two selected protein targets. Results: EtOAc fraction of C. asiatica extract demonstrated strong TYR inhibitory activity with an IC50 of 18.85 μg/mL. TLC profiling of the EtOAc fraction revealed the Rf value of 0.28 for the standard, Rf value of 0.26, 0.21, and 0.15 for the extract, and Rf value of 0.26 and 0.15 for the fraction. Asiaticoside inhibited melanogenesis by elaborating many molecular pathways involving keratinocytes, melanocytes, fibroblast, and endothelial cells by elaborating cytokine, growth factor, extracellular matrix, and melanin degradation enzyme Conclusion: Asiaticoside-rich C. asiatica fraction has the potential as an anti-melanogenesis agent through its TYR inhibitory activity and many molecular pathways.